Assessing Post-Pandemic Mental Health Experiences and Needs Among Marginalized Youth - Rubab, Raiyan; Surendra, Aimee; Biabani, Anam; Youssef, Peter; Amer, Rand; Gravely, Evan (Prepared by the McMaster Research Shop for Abrar Mental Health & Trauma Services, 2025)
Marginalized youth in the Greater Toronto-Hamilton Area continue to face negative mental health outcomes following the COVID-19 pandemic. Abrar Trauma and Mental Health Services is a nonprofit offering culturally appropriate mental health support for newcomers and other diverse populations. Following their 2022 "In This Together" campaign, follow-up was necessary to evaluate the evolving impacts of the pandemic on youth mental health. This research aimed to explore the evolving mental health needs of these youth since the initial pandemic period, as well as explore ways in which marginalized youth access and experience mental health support services in the current post-pandemic era.
Keywords: Hamilton, community-engaged research, youth mental health, pandemic mental health, needs assessment